Gain or loss of diabetogenicity resulting from a single point mutation in recombinant encephalomyocarditis virus. - Jun, H S (1997)
Molecular pathogenic mechanisms for virus-induced disease have received considerable attention. Encephalomyocarditis (EMC) virus-induced diabetes in mice has been extensively studied to elucidate the cellular and molecular mechanisms involved in the development of this disease. In this study, we report for the first time that a single point mutation at nucleotide position 3155 or 3156 of the recombinant EMC viral genome, located on the major capsid protein VP1, which causes an amino acid change, results in the gain or loss of viral diabetogenicity. A G base at nucleotide position 3155 (alanine at amino acid position 776 of the EMC virus polyprotein [Ala776]; GCC) results in viral diabetogenicity, whereas the substitution of other bases at the same or next position results in a loss of viral diabetogenicity. This finding provides clear evidence that a point mutation at a critical site in a viral genome affects the ability of the virus to cause a cell-specific disease.